Lower jaw deformity in triploid Atlantic salmon: an integrated morphological and transcriptomic investigation - Gianluca Amoroso; Ventura, T; Mark Adams; Christopher Carter; Battaglene, SC; Elizur, A; Cobcroft, JM (2015)
Lower jaw deformity (LJD) is a skeletal abnormality that has been commonly reported in farmed Atlantic salmon in several countries at varying prevalence and predominantly in triploids (Benfey, 2001; Sadler et al., 2001; Leclercq et al., 2011; Fraser et al., 2013; Taylor et al., 2013). In Tasmania, LJD can impact up to 30% of commercially produced all-female triploid Atlantic salmon leading to considerable loss to farmers (Hughes, 1992). Our study assessed the effect of ploidy (diploid and triploid) and temperature (14 and 18°C) on the prevalence of several skeletal deformities in all-female Atlantic salmon from 3 to 60 g. The prevalence of LJD was confirmed to be higher in triploids and no temperature effect was observed. Samples of LJD-affected and morphologically normal triploid fish were collected for molecular analysis at the end of the developmental assessment (57.2 ± 1.4 g) when the prevalence of LJD was 10.9 ± 3.5%. Recently, LJD occurrence has been linked to phosphorus deficiency in the diet of triploid salmon (Baeverfjord et al., 2009; Fjelldal et al., 2015). Little is known about the mechanisms underlying LJD in triploids, so we took a transcriptome-wide descriptive approach to examine changes in gene expression in the jaw of normal and LJD-affected triploid fish. In addition, we performed RT-qPCR to test the effect of temperature (standard and high) in normal and LJD-affected triploid fish on the expression of transcripts known to be related to bone and cartilage (i.e. alp, col1a1, mmp13, osteocalcin, trap and col2a1). Analysis of our transcriptomic database implicated numerous genes encoding fundamental structural proteins in LJD, suggesting it is a multigenic-regulated trait. Characterisation and analysis of known roles of the differentially expressed genes suggests that an impairment in cartilage formation might underlie the predisposition to develop LJD, which could be exacerbated by dietary phosphorus deficiency.